Analisis Kinerja Sistem Proteksi Berdasarkan Frekuensi Gangguan Di Gardu Induk 150 KV Garuda Sakti - Ardianto Ardianto; Firdaus Firdaus; Noveri L M (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
With the disruption that can not be predicted, we need a safety equipment (protection system) are precise and reliable. The purpose of this study was to determine the quantity of interference, protection system performance, reliability and power transformer protection system installation requirements in the area power transformer substation of 150 KV Garuda Sakti. Data obtained from the recording in substation Garuda Sakti analyzed using Descriptive Analysis Techniques percentage. The survey results revealed that from 2013 to 2015 occurred 28 times transformer disorders namely: in 2013 occurred 9 times transformer interference, in 2014 occurred 7 times transformer interference, and in 2015 the 12 times the transformer interference. Protection system that works in the event 28 times disruption in Substation Garuda Sakti 2013 to 2015 there are 6 kinds of relays, namely: Rele differential, Rele OCR / GFR, Rele OVR / UVR, Rele REF / SBEF, Rele UVLS and Rele DF / DT is the whole relay has a 100% reliability and got up fairly well. From 2013 to 2015 the reliability of Power Transformer Substation of Garuda Sakti by long outages caused by the interference, the Transformer Power1 reaches the percentage 99.97203%, the Transformer Daya2 reaches 99.983364%, the Transformer Daya3 reach 99.99258% and the Transformer Daya4 reaching 99.99081%. From the data analysis, in general, the protection system in the substation Garuda Sakti it can be argued that meets the requirements of the protection system selectivity, Reliability, Free Labor, Sensitivity and Economic.Keywords: Gardu Induk, Fault, System Protection, Reliability Substation, PLN